Legitimacy Processes and Emotional Responses to Injustice. (June 2016) - Johnson, Cathryn; Hegtvedt, Karen A.; Khanna, Nikki; Scheuerman, Heather L.
People typically respond with negative emotions when they perceive an authority's outcome distribution to be unjust. We argue, however, that legitimacy of the authority—"what others think" in terms of support coworkers and superiors extend to an individual occupying an authority position—acts as an opposing force, attenuating negative emotions and thus helping to sustain stratified orders. Likewise, legitimacy may stymie intentional displays of felt emotions. Our experiment examines the effects of perceived distributive injustice, legitimacy of the authority, and authority's procedural fairness on members' self-reported emotions and likelihood of intended emotional displays toward that authority, a superordinate authority, and coworkers in a work group context. Findings demonstrate that while perceived injustice arouses expected self-reported negative emotions, legitimacy (authorization as support by a superordinate authority and endorsement as support by coworkers) reduces such feelings. Also, strong authorization and endorsement indirectly affect intended emotional displays through self-reported negative emotions.